Spain : Financial Sector Reform: First Progress Report. (IMF Staff Country Reports; Country Report ;, 2012)
The report analyses Spain's financial sector reform program and throws light on the role that the European Financial Stability Facility (EFSF) played in supporting the restructuring and recapitalization of its financial sector. It stated that the two major areas that have been looked at by IMF staff are the macrofinancial context and Spain's progress in financial sector reforms. The key risk factors that hamper economic development are emphasized, and certain measures to overcome the same are suggested.